Tosca: A Drosophila gene encoding a nuclease specifically expressed in the female germline. - Digilio, F.A.; Pannuti, A.; Lucchesi, J.C.; Furia, M.; Polito, L.C. (Developmental Biology, 1996)
We describe here a Drosophila gene, tosca (tos), that is specifically expressed in the female germline. tos mRNA accumulates selectively within the pro-oocyte in germarial region 2 and persists throughout oogenesis. In the early embryo, the maternally supplied tos mRNA is evenly distributed at the syncytial blastoderm stage, but is excluded from the forming cells when cellularization begins. tos product is the first Drosophila member of the RAD2 protein family, a group of related DNA repair nucleases conserved from yeast to humans. Within the family, Tos is more closely related to ExoI, a Schizosaccharomyces pombe 5'-->3' double-stranded DNA exonuclease specifically induced in meiotic prophase I. The definite oocyte localization of tos transcript during meiosis and its ubiquitous distribution in early embryos suggest that tos may play a role in mismatch repair during genetic recombination and early cleavage divisions.